Novel sulfur storage-catalysis integrated lithium-sulfur battery electrode design method
By using porous carbon materials to load sulfur and prepare polysulfide catalysts in lithium sulfur batteries, combined with beating technology of mixed binders and conductive agents, it is applied successively, and undergoes aqueous phase transformation and freeze-drying to prepare sulfur storage-catalytic integrated electrodes, which solves a series of problems in the circulation process of lithium sulfur batteries and achieves efficient electrochemical performance and safety.
Patent Information
- Application Number
- CN202411679025.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
During the circulation process, lithium-sulfur batteries have problems such as low utilization rate of active substances, poor discharge capacity, decreased capacity, decreased circulation performance and safety hazards.
Porous carbon materials are loaded with elemental sulfur and a high-efficiency catalyst with polysulfide catalytic activity is prepared. By mixing binder and conductive agent, slurry, coating, aqueous phase transformation and freeze-drying, sulfur storage-catalytic integrated lithium sulfur battery electrode is prepared.
It realizes the catalytic conversion capacity of high-efficiency sulfur-carrying and polysulfides, improves the cycle stability and electrochemical performance of the battery, and reduces safety risks.
Smart Images

Figure CN119581474A_ABST
Abstract
Description
Technical Field
[0001] A novel sulfur storage-catalysis integrated lithium-sulfur battery electrode design method, belonging to the field of electrochemistry Background Art
[0002] Among the new high energy storage battery systems, lithium-sulfur batteries are a branch that has been studied more and developed more rapidly. The biggest advantage of this battery system is its very high theoretical capacity. If calculated with elemental sulfur as the positive electrode, the theoretical capacity of lithium-sulfur batteries can reach 1675mA hg -1 The theoretical energy density can reach 2600W h kg -1 , far higher than the general lithium-ion battery system, second only to the lithium-air battery, whose research progress is slow. At the same time, sulfur is cheap, abundant in resources, and environmentally friendly. These combined factors make the further commercialization of lithium-sulfur batteries have great potential. Therefore, lithium-sulfur batteries are regarded as the most anticipated next-generation electrochemical energy storage system.
[0003] Lithium-sulfur batteries still have their own problems. First, the electronic conductivity and ionic conductivity of the active material sulfur and the discharge product lithium sulfide are extremely low, resulting in low utilization of active materials and poor high-current discharge capacity. Second, the intermediate product of the electrochemical reaction, lithium polysulfide, is easily soluble in organic electrolytes. Driven by concentration differences and electric field forces, it migrates back and forth between the positive and negative electrodes, resulting in a shuttle effect, causing the battery capacity to decrease and the cycle performance to decrease. Third, during the charge and discharge reaction, due to the different densities of the active material sulfur and the final discharge product lithium sulfide, a volume change of about 80% occurs, causing the electrode structure to be destroyed, the battery to become unstable, and the battery electrochemical performance to be affected. Finally, the use of highly active metallic lithium as the counter electrode causes volume changes and lithium dendrite growth during the cycle, which can easily puncture the diaphragm, causing the battery to short-circuit, posing serious safety hazards.
[0004] Therefore, there is an urgent need for an electrode that can simultaneously realize the transfer of sulfur and has catalytic conversion capabilities to solve the problems in the lithium-sulfur battery cycle. Summary of the invention
[0005] In view of the problems existing in the existing preparation technology, the purpose of the present invention is to propose a new sulfur storage-catalysis integrated lithium-sulfur battery electrode design method. This flexible electrode preparation method is simple and easy.
[0006] The present invention provides a novel sulfur storage-catalysis integrated lithium-sulfur battery electrode design method, comprising: loading elemental sulfur with a porous carbon material; preparing a high-efficiency catalyst with polysulfide catalytic activity; preparing a mixed binder for integrated electrode preparation; using the mixed binder in combination with a conductive agent to slurry the porous carbon material and the catalytic material after sulfur loading, respectively; coating the prepared slurry on a glass plate in a certain thickness; transferring the glass plate coated with the slurry to an aqueous solution of CNT for water phase transformation; and finally drying the electrode after the phase transformation using a freeze-drying technology to prepare a sulfur storage-catalysis integrated lithium-sulfur battery electrode.
[0007] Preferably, the porous carbon material is a high specific surface area material prepared by activation, and its specific surface area is greater than 2000m 2 g -1 The sulfur loading can include melting, gas phase and liquid phase sulfur loading.
[0008] Preferably, the polysulfide catalytic material includes transition metal sulfides / oxides, and composite materials thereof with materials such as CNTs.
[0009] Preferably, the conductive agent material includes highly active conductive materials such as super p, carbon black, KB, CNT, and CNF.
[0010] Preferably, the novel mixed binder is a mixed binder such as PAN / TPU, PAN / PVDF, PAN / PEO, etc., and the ratio between the mixed binders is 10:0-0:10.
[0011] Preferably, the feed mass ratio of the sulfur-carrying active material and the catalytic material to the conductive agent and the mixed binder is 1:1-8:1.
[0012] Preferably, the stepwise coating process includes controlling the coating thickness of the sulfur-carrying active material to be 100-500 μm; and continuously coating the catalytic layer on the sulfur-carrying layer, controlling the thickness of the catalytic layer to be 20-100 μm.
[0013] Preferably, the phase transition solution is a CNT aqueous dispersion, wherein the concentration of CNT is less than 0.001 wt %.
[0014] Preferably, the freeze-drying process needs to ensure the overall flatness of the electrode, and before freeze-drying, it needs to ensure that the phase transformation is fully carried out, and the cold trap temperature is required to be less than -50°C.
[0015] The method of the invention is simple and easy to implement. According to the preparation method of the invention, the method for preparing a sulfur storage-catalysis integrated lithium-sulfur battery electrode has the ability of efficient sulfur loading and polysulfide catalytic conversion, and gradually applies and then performs a phase transformation to realize the construction of a sulfur storage-catalysis integrated structure. The mixed binder is cross-linked and polymerized into a three-dimensional network structure under the action of the phase transformation. The conductive agent is compounded in the three-dimensional network during the phase transformation process to form an internal three-dimensional conductive network. The CNT in the CNT aqueous solution for phase transformation is dispersed in the middle of the three-dimensional conductive network under the action of surface tension to form an external conductive network. At the same time, the porous structure is conducive to the infiltration of the electrolyte and improves the electrode reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings, in which:
[0017] Figure 1 The working principle diagram of the sulfur storage-catalysis integrated electrode
[0018] Figure 2 SEM cross-sectional view of the sulfur storage-catalysis integrated electrode
[0019] Figure 3 Thickness measurement diagram of sulfur storage-catalysis integrated electrode
[0020] Figure 4 This is the cycling performance diagram of the sulfur storage-catalysis integrated electrode at a current density of 0.2C. DETAILED DESCRIPTION
[0021] The present invention is further described below in conjunction with the accompanying drawings and the following specific embodiments. It should be understood that the following embodiments and / or drawings are only used to illustrate the present invention rather than to limit the present invention.
[0022] The above-mentioned invention object of the present invention is preferably achieved through the following technical solutions:
[0023] a) using porous carbon materials to load elemental sulfur;
[0024] b) preparing a highly efficient catalyst having polysulfide catalytic activity;
[0025] c) preparing a mixed binder for integrated electrode preparation;
[0026] d) using a mixed binder and a conductive agent to slurry the porous carbon material and the catalytic material after the sulfur is loaded;
[0027] e) coating the prepared slurry evenly on the glass plate in a certain thickness;
[0028] f) transferring the glass plate coated with the slurry to an aqueous solution of CNTs for aqueous phase transition;
[0029] g) The electrode after the phase transformation is finally dried using freeze-drying technology to prepare a sulfur storage-catalysis integrated lithium-sulfur battery electrode.
[0030] Preferably, the porous carbon material in step a) is a high specific surface area material prepared by activation, and its specific surface area is greater than 2000 m 2 g -1 The sulfur loading can include melting, gas phase and liquid phase sulfur loading, with a sulfur loading amount of 60%-80%.
[0031] Preferably, the polysulfide catalytic material in step b) includes transition metal sulfides / oxides, and composite materials thereof with materials such as CNTs.
[0032] Preferably, the novel mixed binder in step c) is a mixed binder such as PAN / TPU, PAN / PVDF, PAN / PEO, etc., and the ratio between the mixed binders is 10:1-1:1.
[0033] Preferably, the conductive agent material in step d) includes highly active conductive materials such as super p, carbon black, KB, CNT, CNF, etc.
[0034] Preferably, in step d), the mass ratio of the sulfur-carrying active material and the catalytic material to the conductive agent and the mixed binder is 1:1-8:1.
[0035] Preferably, the process of the successive coating in step e) includes controlling the coating thickness of the sulfur-carrying active material to be 100-500 μm; and continuously coating the catalytic layer on the sulfur-carrying layer, controlling the thickness of the catalytic layer to be 20-100 μm.
[0036] Preferably, the phase conversion solution in step f) is a CNT aqueous dispersion, wherein the concentration of CNT is less than 0.001 wt%.
[0037] Preferably, the freeze-drying process in step g) needs to ensure the overall flatness of the electrode, and before freeze-drying, it needs to ensure that the phase transformation is fully carried out, and the cold trap temperature is required to be less than -50°C.
[0038] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The following examples of specific sulfur-carrying materials, catalytic materials, conductive agents, types of mixed binders, solid content of slurry, coating thickness, and solutions used for phase transition are also only examples within a suitable range, that is, those skilled in the art can choose within a suitable range through the description of this article, and are not limited to the specific values exemplified below.
[0039] Example 1
[0040] 1) PAN / TPU was used as a mixed binder with a ratio of PAN:TPU=8:2 and a solvent of DMF. The mixture was magnetically stirred at room temperature for 12 hours to obtain a 10 wt% P8T2 binder.
[0041] 2) Microporous carbon was prepared using silk as the carbon source and ZnCl2 as the pore-forming activator.
[0042] 3) The porous carbon and elemental sulfur were mixed in a ratio of 3:7, transferred to a polytetrafluoroethylene liner, and kept at 155°C for 16 hours.
[0043] 4) Using the hydrothermal method, MoS2 / CNT composite one-dimensional materials were prepared for use as polysulfide catalytic materials.
[0044] 5) The carbon-sulfur composite material and catalytic material after sulfur storage were mixed with P8T2 binder, KB, and CNF in a ratio of 70:20:5:5 and slurried as slurry A and slurry B respectively.
[0045] 6) Slurry A was applied onto a glass plate using a 400 μm doctor blade, and slurry B was applied onto slurry A using a 500 μm doctor blade.
[0046] 7) Placing the glass plate coated with the active material in a CNT dispersion to undergo phase transition until the solvent exchange is completed.
[0047] 8) Take out the electrode after phase transformation, freeze it from bottom to top with liquid nitrogen, and freeze-dry it in vacuum.
[0048] The obtained electrode film was cut into discs with a diameter of 10 mm, and the cut electrode pieces were used as positive electrodes, metal lithium sheets as negative electrodes, polypropylene microporous membranes (Celgard 2400) as separators, and ether electrolytes were used, wherein the catalyst layer was in contact with the separator, and button cells were assembled to test their electrochemical properties. The charge and discharge cycle performance was as follows: Figure 4 . At 0.2C (1C = 1670mAg -1) current density, the first reversible specific capacity is 1280 mAh g -1 After 200 cycles, the discharge capacity is 676, which has good cycle stability. Figure 1 As shown, the electrode picture is as Figure 2 and 3 shown.
[0049] Example 2
[0050] 1) PAN / TPU was used as a mixed binder with a ratio of PAN:TPU=8:2 and a solvent of DMF. The mixture was magnetically stirred at room temperature for 12 hours to obtain a 10 wt% P8T2 binder.
[0051] 2) Use commercial high specific surface area porous carbon as the carbon source.
[0052] 3) The porous carbon and elemental sulfur were mixed in a ratio of 3:7, transferred to a polytetrafluoroethylene liner, and kept at 155°C for 16 hours.
[0053] 4) Using the hydrothermal method, MoS2 / CNT composite one-dimensional materials were prepared for use as polysulfide catalytic materials.
[0054] 5) The carbon-sulfur composite material and catalytic material after sulfur storage were mixed with P8T2 binder, KB, and CNF in a ratio of 70:20:5:5 and slurried as slurry A and slurry B respectively.
[0055] 6) Slurry A was applied onto a glass plate using a 400 μm doctor blade, and slurry B was applied onto slurry A using a 500 μm doctor blade.
[0056] 7) Placing the glass plate coated with the active material in a CNT dispersion to undergo phase transition until the solvent exchange is completed.
[0057] 8) Take out the electrode after phase transformation, freeze it from bottom to top with liquid nitrogen, and freeze-dry it in vacuum.
[0058] The obtained electrode film was cut into discs with a diameter of 10 mm, and the cut electrode pieces were used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane (Celgard 2400) was used as the separator, and an ether electrolyte was used, in which the catalyst layer was in contact with the separator, to assemble a button cell and test its electrochemical performance.
[0059] Example 3
[0060] 1) PAN / TPU was used as a mixed binder with a ratio of PAN:TPU=8:2 and a solvent of DMF. The mixture was magnetically stirred at room temperature for 12 hours to obtain a 10 wt% P8T2 binder.
[0061] 2) Use commercial high specific surface area porous carbon as the carbon source.
[0062] 3) The porous carbon and elemental sulfur were mixed in a ratio of 3:7, transferred to a polytetrafluoroethylene liner, and kept at 155°C for 16 hours.
[0063] 4) Use commercial MoS2 as the catalytic material.
[0064] 5) The carbon-sulfur composite material and catalytic material after sulfur storage were mixed with P8T2 binder, KB, and CNF in a ratio of 70:20:5:5 and slurried as slurry A and slurry B respectively.
[0065] 6) Slurry A was applied onto a glass plate using a 400 μm doctor blade, and slurry B was applied onto slurry A using a 500 μm doctor blade.
[0066] 7) Placing the glass plate coated with the active material in a CNT dispersion to undergo phase transition until the solvent exchange is completed.
[0067] 8) Take out the electrode after phase transformation, freeze it from bottom to top with liquid nitrogen, and freeze-dry it in vacuum.
[0068] The obtained electrode film was cut into discs with a diameter of 10 mm, and the cut electrode pieces were used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane (Celgard 2400) was used as the separator, and an ether electrolyte was used, in which the catalyst layer was in contact with the separator, to assemble a button cell and test its electrochemical performance.
[0069] Finally, it should be noted that the above embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above contents of the present invention all fall within the scope of protection of the present invention.
Claims
1. A novel sulfur storage-catalysis integrated lithium-sulfur battery electrode design method, characterized in that: include: Using porous carbon materials to load elemental sulfur; Preparation of highly efficient catalysts with polysulfide catalytic activity; preparing a mixed binder for integrated electrode preparation; The sulfur-loaded porous carbon material and the catalytic material are slurried respectively using a mixed binder combined with a conductive agent; The prepared slurry is evenly coated on the glass plate in a certain thickness; The glass plate coated with the slurry was transferred to an aqueous solution of CNTs for aqueous phase transition; The electrode after the phase transformation is finally dried using freeze-drying technology to prepare a sulfur storage-catalysis integrated lithium-sulfur battery electrode. The porous carbon material may be loaded with sulfur by melting, gas phase and liquid phase method; The polysulfide catalyst may be any catalyst having a polysulfide catalytic function; The mixed binder is a mixed binder such as PAN / TPU, PAN / PVDF, PAN / PEO, etc., and the ratio between the mixed binders is 10:0-0:10; The separate slurrying includes mixing and slurrying the mixed binder with the conductive agent and the porous carbon material loaded with sulfur in a certain proportion to prepare a sulfur-loaded active material slurry; mixing and slurrying the mixed binder with the conductive agent and the catalytic material in a certain proportion to prepare a catalytic material slurry; The slurry is applied successively by first applying the active material slurry on the glass plate, and then replacing scrapers of different thicknesses to apply the catalytic material slurry on the previous slurry; The aqueous solution of CNT is a CNT dispersion uniformly dispersed in a certain proportion; Before freeze drying, it is necessary to ensure that the phase transition is fully carried out and the cold trap temperature is required to be less than -50°C.
2. The preparation method according to claim 1, characterized in that: The sulfur loading amount of the porous carbon material is 60%-90%.
3. The preparation method according to claim 1, characterized in that: The polysulfide catalytic material includes transition metal sulfides / oxides and the like.
4. The preparation method according to claim 1, characterized in that: The conductive agent material includes highly active conductive materials such as super p, carbon black, KB, CNT, CNF, etc.
5. The preparation method according to claim 1, characterized in that: The prepared mixed adhesive comprises various hard segment polymers with supporting structures and polymers with flexible segment structures, and the ratio between the two is 10:0-0:
10.
6. The preparation method according to claim 1, characterized in that: The feed mass ratio of the sulfur-carrying active material and the catalytic material to the conductive agent and the mixed binder is 1:1-8:
1.
7. The preparation method according to claim 1, characterized in that: The step-by-step coating process includes controlling the coating thickness of the sulfur-carrying active material to be 100-500 μm; and continuously coating the catalytic layer on the sulfur-carrying layer, controlling the thickness of the catalytic layer to be 20-100 μm.
8. The preparation method according to claim 1, characterized in that: The phase transition solution is a CNT aqueous dispersion, wherein the concentration of CNT is less than 0.001 wt %.
Citation Information
Patent Citations
Sulfur electrode, and preparation and application thereof
CN102903887A
Lithium sulfur battery membrane material and application thereof
CN106848156A
Integrated porous polypyrrole carrier sodium electrode and sulfur electrode preparation method
CN110350142A
Sulfur-carrying material and positive electrode material of lithium-sulfur battery
CN111403702A
Co-NCNT (at) HC hierarchical pore carbon material and preparation method and application thereof
CN115072696A